Plautus’ Epidicus 1–305: introduction, text, translation, commentary - Harman, Robert Sean (2016)
Plautus’ Epidicus focuses on the titular cunning slave, who is on stage for all but 15 of these first 305 lines, and his attempts to rescue himself from certain punishment, after his initial scheme almost collapses with news of a change of heart from his young master. He brings about a dizzying number of deceptions to extricate himself, eventually winning his freedom at the expense of virtually every other character.